2021
DOI: 10.14202/ijoh.2021.237-245
|View full text |Cite
|
Sign up to set email alerts
|

Rift valley fever in Africa with the emerging interest in Libya

Abstract: Rift valley fever (RVF) is an acute vector-borne viral zoonotic disease of domestic and wild ruminants. The RVF virus (RVFV) belonging to the Phlebovirus genus of the Bunyaviridae family causes this disease. Studies have shown that mosquitoes are the vectors that transmit RVFV. Specifically, Aedes and Culex mosquito species are among the many vectors of this virus, which affects not only sheep, goats, buffalo, cattle, and camels but also human beings. Since the 30s of the last century, RVF struck Africa, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Both cutaneous leishmaniasis (CL) and visceral leishmaniasis (VL) are also endemic, with nearly 1000 human CL cases reported each year since 1980, the majority resulting from zoonotic and anthroponotic transmission [ 19 21 ]. In comparison, RVF is an emerging zoonotic disease of concern, with the first animal outbreak reported by officials in December 2019 detected in a flock of sheep and goats [ 22 , 23 ]. In 2014, Libya reported its first and only outbreak of HPAI H5N1 in poultry which spread to humans, resulting in 10 cases and 5 fatalities [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cutaneous leishmaniasis (CL) and visceral leishmaniasis (VL) are also endemic, with nearly 1000 human CL cases reported each year since 1980, the majority resulting from zoonotic and anthroponotic transmission [ 19 21 ]. In comparison, RVF is an emerging zoonotic disease of concern, with the first animal outbreak reported by officials in December 2019 detected in a flock of sheep and goats [ 22 , 23 ]. In 2014, Libya reported its first and only outbreak of HPAI H5N1 in poultry which spread to humans, resulting in 10 cases and 5 fatalities [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brucellosis and RVF, the Libyan context. Libya is at high risk for future brucellosis and RVF outbreaks, as it borders endemic and enzootic countries Niger, Sudan, and Egypt and livestock trade movement, both legal and illegal, is known to occur [23]. The majority of cases are attributed to intensive importation of livestock for breeding [17]; sheep and goats play an important role in religious and cultural festivals [29].…”
Section: Priority Zoonotic Diseases In Libyamentioning
confidence: 99%
“…The potential expansion of RVFV out of its current range could be driven by several known processes that have already demonstrated the capacity to move other pathogens within and between countries and continents. Tens of thousands of instances of movement of ungulate livestock and wildlife for legal and illegal trade—as well as natural ranging of wildlife—take place each year within and between RVFV endemic and nonendemic areas, risking virus importation (Bird et al 2007, Cêtre-Sossah et al 2012, Kenawy et al 2018, Métras et al 2020, Youssouf et al 2020, Mahmoud et al 2021). Shipping containers and other freight that can harbor infected mosquito eggs, immatures, or adults are also rapidly moved by the hundreds of thousands by air, sea, and land between these areas (Hufnagel et al 2004, Fitzgibbon et al 2020, Trájer 2021).…”
Section: The Frontier Of Expansionmentioning
confidence: 99%
“…This outbreak went unrecognized and unreported until late in the epidemic 2 traveling French physicians happened to observe unusually high cases of human sickness and called for surveillance (Walsh 1988, Digoutte and Peters 1989). Recently, more serological studies are being conducted within and adjacent to RVFV endemic countries where the virus has not been reported for extended periods such as in Uganda (Shoemaker et al 2019), or has never been reported such as in Turkey (Tezcan-Ulger et al 2019) or Libya (Mahmoud et al 2021), revealing recent RVFV activity in livestock and humans. It is possible that interepizootic transmission of RVFV has always been high but has not been the subject of surveillance.…”
Section: The Frontier Of Expansionmentioning
confidence: 99%
“…Many transboundary animal diseases (TADs) have been reported in Libya during the past few years, and instability in Libya has made it difficult to implement surveillance and monitoring programs for emerging and re-emerging infectious diseases with significant public health and socioeconomic impacts [10]. However, high commercial livestock activities in the country, especially in the hotspot (risky) areas where illegal animals cross the border from historically infected countries, make these areas pathways and portals of entrance to many TADs and increase the risk of emerging and re-emerging infectious diseases on a regional level [15][16][17]. In Libya, transitional animal movement is not well controlled between cities, and the extensive trade of livestock on a regional level increases the potential risk of the introduction of infected animals from neighboring endemic regions [18,19].…”
Section: Introductionmentioning
confidence: 99%